Analysis of the Tourism Economic Effects Reach in European Union Member States - Petrović, Gordana; Karabašević, Darjan; Vukotić, Svetlana; Mirčetić, Vuk (Turizam, 2020)
The paper aims to analyze the impact of the tourism industry on the economy of the European Union. In this context, the paper is based on research and literature review, in particular, statistics data of Eurostat and the World Travel and Tourism Council. The results achieved by the tourism industry are reflected through certain economic indicators: GDP, employment rate, income, the balance of payments, turnover and consumption. The research area is one of the most visited tourist destinations in the world, which generates significant tourist turnover and justifies the status of an extremely important determinant of economic development. The well managed tourism industry complements other economic activities and increases the income of each EU Member State, and the tourism industry has direct and indirect, positive and negative economic effects.